Jinnah and British Balochistan: Dynamics of Political Mobilization During the Struggle for Pakistan - Dar, Farooq Ahmad (JSSH, 2026)
This paper examines Quaid-i-Azam Mohammad Ali Jinnah’s policy and political strategy toward colonial Balochistan, focusing exclusively on the British Administrative Districts, while setting aside the princely states and tribal territories existed in the province. Largely based on primary sources, the study aims to explore how Jinnah viewed Balochistan’s political significance within the broader framework of the Pakistan Movement and how he nurtured political awareness and support in this otherwise politically deprived province. The paper investigates Jinnah’s connectivity with the people and leadership of Balochistan, his strategy to win over the electoral college comprising of Shahi Jirga and the non-official members of the Quetta Municipality, and his dealing with the colonial administrative mechanism of the province. It argues that Jinnah’s commitment to the Balochistan cause and his strategy to convince the local populace managed to align British Balochistan with the demand for Pakistan